Analysis of the banking industry in Indonesia through the Structure-Conduct-Performance approach - Saifudin Zuhri (Nur Science Institute, 2024)
The economy is the leading indicator of a country's progress seen from the financial services sector. The role of banking is to help the community and accelerate economic turnover. This study aims to determine the structure, behavior, and performance of the banking industry in Indonesia. The data in this study used the Annual Financial Statements of Banks in Indonesia in 2020. The analytical tools used are the Concentration Ratio (CR), the Herfindahl Hirschman Index (HHI), and Market Entry Barriers. The results of the SCP analysis show that the Indonesian banking industry has a high oligopoly market structure where the decision-making of a company can affect other companies; the MES value of the Banking industry between 49.38 percent and 53.48 percent indicates that in the banking industry, it is tough for new competitors to compete with banking companies that already control the market. Regarding behavioral strategies, the banking industry should pay attention to technological innovation, ease of access, and determination of community market share. In terms of company performance, based on the return on asset data and return on equity, PT Bank Central Asia is the company with the best and most stable profitability performance.